Ответы и объяснения

2012-04-26T12:49:20+00:00
Лучший Ответ!
2012-04-26T12:55:39+00:00

А1

а) \frac{5a+10}{b-7}:\frac{a^2+4a+4}{2b-14}=\frac{5(a+2)2(b-7)}{(b-7)(a+2)^2}=\frac{10}{a+2}

б) \frac{\sqrt{50}\sqrt{6}}{\sqrt{12}}=\sqrt\frac{50*6}{12}}=\sqrt25}=5

А2

а) \frac{(\sqrt{2})^6}{32}=\frac{8}{32}=\frac{1}{4}

б) (5.2*10^{-7})(3.5*10^4)=18.2*10^{-3}

в) \frac{3^{-6}9^{-2}}{3^{-12}}=\frac{3^{-6}3^{-4}}{3^{-12}}=3^{-6-4+12}=9

А3 x^2+2x=16x-49

x^2-14x+49=0 

(x-7)^2=0 

x=7 

А4 \left \{ {{6x+1\geq1+4x} \atop {5x<4+10x}} \right.

\left \{ {{2x\geq0} \atop {5x>-4}} \right. 

\left \{ {{x\geq0} \atop {x>-\frac{4}{5}}} \right. 

x [0;+\infty) 

В1 x^3-3x^2-4x+12=0

x(x^2-4)-3(x^2-4)=0 

(x-3)(x-2)(x+2)=0 

x = -2; x= 2; x=3